2021
DOI: 10.1021/acs.jpca.1c01102
|View full text |Cite
|
Sign up to set email alerts
|

Short Iterative Lanczos Integration in Time-Dependent Equation-of-Motion Coupled-Cluster Theory

Abstract: A time-dependent (TD) formulation of equation-of-motion coupled-cluster (EOM-CC) theory can provide excited-state information over an arbitrarily wide energy window with a reduced memory footprint relative to conventional, frequency-domain EOM-CC theory. However, the floating-point costs of the time-integration required by TD-EOM-CC are generally far larger than those of the frequency-domain form of the approach. This work considers the potential of the short iterative Lanczos (SIL) integration scheme [J. Chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…Real-time coupled cluster (RT-CC) methods, in particular, can achieve exceptionally high accuracy in many cases , and have been explored in the context of real-time simulations for some years. , However, RT-CC approaches also suffer from the same affliction as that of their time-independent counterparts, namely, high-degree polynomial scaling with the size of the molecular system. For ground-state coupled cluster theory, techniques, such as local correlation, fragmentation, tensor decomposition, and others, have been developed to permit applications to larger molecular systems than conventional implementations allow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real-time coupled cluster (RT-CC) methods, in particular, can achieve exceptionally high accuracy in many cases , and have been explored in the context of real-time simulations for some years. , However, RT-CC approaches also suffer from the same affliction as that of their time-independent counterparts, namely, high-degree polynomial scaling with the size of the molecular system. For ground-state coupled cluster theory, techniques, such as local correlation, fragmentation, tensor decomposition, and others, have been developed to permit applications to larger molecular systems than conventional implementations allow.…”
Section: Introductionmentioning
confidence: 99%
“…For the application to core excitation spectra, Bartlett and co-workers , compared time-independent (TI) EOM-CC and time-dependent (TD) EOM-CCas well as contributions beyond the dipole approximationand concluded that TD-EOM-CC can provide accurate spectra for both core and valence spectra. In addition, in 2021, Li, DePrince, and co-workers applied the short iterative Lanczos integration to the time-dependent (TD) EOM-CC method for a more efficient calculation of K-edge spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Time-dependent CC formulations, which provide an alternative way of describing excited-state processes, have attracted significant attention in the last decade. [50][51][52][53][54][55][56] In this context, we have recently developed a real-time equation-of-motion CC (RT-EOM-CC) method [57][58][59][60] to compute the one-electron GF based on a CCSD cumulant approach, which provides several advantages compared to other excited-state formulations. For example, the approach leads to an explicit exponential cumulant representation of the Green's function [61] and, at the same time, allows one to formulate a non-perturbative expression for the cumulant in terms of the solutions to a set of coupled, first-order nonlinear differential equations for the CC amplitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Real-time coupled cluster (RT-CC) methods, in particular, can achieve exceptionally high accuracy in many cases 17,18 and have been explored in the context of real-time simulations for some years. [9][10][11][19][20][21][22][23][24][25][26][27] However, RT-CC approaches also suffer from the same affliction as that of their time-independent counterparts, viz., high-degree polynomial scaling with the size of the molecular system. For ground-state coupled cluster theory, techniques such as local correlation, [28][29][30][31][32][33][34][35] fragmentation, [36][37][38][39] tensor decomposition, [40][41][42][43][44][45] and others have been developed to permit applications to larger molecular systems than conventional implementations allow.…”
Section: Introductionmentioning
confidence: 99%
“…For the application to core excitation spectra, Bartlett and coworkers 25,26 compared timeindependent (TI) EOM-CC and time-dependent (TD) EOM-CC -as well as contributions beyond the dipole approximation -and concluded that TD-EOM-CC can provide accurate spectra for both core and valance spectra. In addition, in 2021, Li, DePrince, and co-workers 27 applied the short iterative Lanczos integration to the time-dependent (TD) EOM-CC method for a more efficient calculation of K-edge spectra.…”
Section: Introductionmentioning
confidence: 99%